2016
DOI: 10.1038/srep29419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the induction of preproinsulin-specific Foxp3+ CD4+ Treg cells that inhibit CD8+ T cell-mediated autoimmune diabetes by DNA vaccination

Abstract: DNA vaccination is a promising strategy to induce effector T cells but also regulatory Foxp3+ CD25+ CD4+ Treg cells and inhibit autoimmune disorders such as type 1 diabetes. Little is known about the antigen requirements that facilitate priming of Treg cells but not autoreactive effector CD8+ T cells. We have shown that the injection of preproinsulin (ppins)-expressing pCI/ppins vector into PD-1- or PD-L1-deficient mice induced Kb/A12-21-monospecific CD8+ T cells and autoimmune diabetes. A pCI/ppinsΔA12-21 vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
(99 reference statements)
0
11
0
Order By: Relevance
“…In this study, LR1 increased the production of cytokines IL-22 and TGF-β associated with inhibiting TLR4 expression in the ileum of weaned pigs. Previous studies showed that TGF-β down-regulates inflammatory cytokine production in monocytes and macrophages (Laine et al, 2004) and plays a role in the induction from CD4 + T cells of induced immune regulatory T cells (Stifter et al, 2016). IL-22 is produced by activated NK and T cells, and initiates innate immune responses against pathogens invasion especially in the intestinal epithelial cells (Trevejo-Nunez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, LR1 increased the production of cytokines IL-22 and TGF-β associated with inhibiting TLR4 expression in the ileum of weaned pigs. Previous studies showed that TGF-β down-regulates inflammatory cytokine production in monocytes and macrophages (Laine et al, 2004) and plays a role in the induction from CD4 + T cells of induced immune regulatory T cells (Stifter et al, 2016). IL-22 is produced by activated NK and T cells, and initiates innate immune responses against pathogens invasion especially in the intestinal epithelial cells (Trevejo-Nunez et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that injection of pCI/ppins but not pCI/ppinsΔA 12-21 DNA into H-2 b PD-1- or PD-L1-deficient mice induced CD8 + T cell-mediated autoimmune diabetes (Figures S1B and S1C) 7, 8. However, the failure to induce CD8 + T cells in PD-1 −/− and PD-L1 −/− mice by pCI/ppinsΔA 12-21 facilitated the induction of a systemic Foxp3 + CD25 + CD4 + Treg cell immunity that suppressed diabetes development by de novo primed K b /A 12-21 -specific CD8 + T cells 18 . Similarly, pCI/GFP-ppins or pCI/NLS-ppins vectors did not induce autoimmune diabetes in PD-L1-deficient mice (Figure 3A) and efficiently suppressed CD8 + T-cell-mediated diabetes induction by a subsequent injection of the pCI/ppins vector (Figure 3B).…”
Section: Resultsmentioning
confidence: 98%
“…In line with our previous findings, injection of pCI/GFP-ppins significantly increased Foxp3 + CD25 + CD4 + Treg cell frequencies in PD-L1 −/− mice (Figure S4). 18 This confirmed that ppins antigens that primarily did not induce autoreactive CD8 + T cells are immunogenic and induced an immune-suppressive immunity that controls de novo priming and/or expansion of K b /A 12-21 -specific effector CD8 + T cells in this diabetes model 18 Figure 3Determination of the Immune-Suppressive Potential of pCI/GFP-ppins and pCI/NLS-pins in PD-L1 −/− Mice(A) PD-L1 −/− mice were either immunized with pCI/ppins (n = 9), pCI/GFP-ppins (n = 5), or pCI/NLS-pins alone (n = 5) (left) or immunized with pCI/GFP-ppins or pCI/NLS-pins (n = 5 per group) followed by the injection of the diabetes-inducing pCI/ppins vector at day 12 post-vaccination (right).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 1 diabetes is characterized by T lymphocytes‐mediated destruction of pancreatic β‐cells, and CD4 + T lymphocytes are important in recognizing islet autoantigens, especially hybrid insulin peptides and proinsulin, and prompting pancreatic infiltration in autoimmune diabetes. Aside from T cell‐mediated immunity, the destruction of β‐cells also leads to a humoral response with production of antibodies against β‐cell autoantigens, with glutamic acid decarboxylase antibody (GADA) being the most common antibody present in autoimmune diabetes.…”
Section: Introductionmentioning
confidence: 99%